Eco-Friendly Synthesis Procedure for the Reduction of o-Hydroxy Acetophenone: - (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Microbial catalyst reduction of o-amino acetophenone was with free Beaker’s yeast(Saccharomyces Cerevisiae) as well as immobilized Beaker’s yeast in alcoholic medium. The reductionproduct was isolated and purified by basis of its spectral analysis.